Interaction of Halictine-Related Antimicrobial Peptides with Membrane Models - Pazderková, Markéta; Maloň, Petr; Zíma, Vlastimil; Hofbauerová, Kateřina; Kopecký, Vladimír; Kočišová, Eva; Pazderka, Tomáš; Čeřovský, Václav; Bednárová, Lucie (International journal of molecular sciences, 2019)
We have investigated structural changes of peptides related to antimicrobial peptide Halictine-1 (HAL-1) induced by interaction with various membrane-mimicking models with the aim to identify a mechanism of the peptide mode of action and to find a correlation between changes of primary/secondary structure and biological activity. Modifications in the HAL-1 amino acid sequence at particular positions, causing an increase of amphipathicity (Arg/Lys exchange), restricted mobility (insertion of Pro) and consequent changes in antimicrobial and hemolytic activity, led to different behavior towards model membranes. Secondary structure changes induced by peptide-membrane interaction were studied by circular dichroism, infrared spectroscopy, and fluorescence spectroscopy. The experimental results were complemented by molecular dynamics calculations. An α-helical structure has been found to be necessary but not completely sufficient for the HAL-1 peptides antimicrobial action. The role of alternative conformations (such as β-sheet, PPII or 310-helix) also seems to be important. A mechanism of the peptide mode of action probably involves formation of peptide assemblies (possibly membrane pores), which disrupt bacterial membrane and, consequently, allow membrane penetration.
Keywords: Hydrophobic and Hydrophilic Interactions; Phosphatidylglycerols; fosfatidylglyceroly; circular dichroism; Lipid Bilayers; permeabilita; simulace molekulární dynamiky; konformace proteinů, beta-řetězec; Phosphatidylcholines; hydrofobní a hydrofilní interakce; antibacterial peptides; kationické antimikrobiální peptidy; Protein Conformation, beta-Strand; antibakteriální látky; Molecular Dynamics Simulation; lipidové dvojvrstvy; Amino Acid Sequence; konformace proteinů, alfa-helix; infrared spectroscopy; Permeability; kinetika; Anti-Bacterial Agents; Protein Conformation, alpha-Helical; Antimicrobial Cationic Peptides; fluorescence; sekvence aminokyselin; fosfatidylcholiny; halictine; Kinetics